2019
DOI: 10.2147/tcrm.s188941
|View full text |Cite
|
Sign up to set email alerts
|

<p>Vitamin D supplementation for the prevention or depletion of side effects of therapy with alemtuzumab in multiple sclerosis</p>

Abstract: Purpose of review: Not only the multiple sclerosis specialist but also the general neurologist and primary care practitioner are increasingly aware of possible adverse events (AEs) by treatment with alemtuzumab (over 47% risk of secondary autoimmune-mediated diseases). Vitamin D supplementation's effect (VDS) to reduce these autoimmune AEs is poorly performed in routine practice. This article seeks to justify why this simple, inexpensive, patient-friendly therapy should be seriously discussed. Recent findings:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 119 publications
(135 reference statements)
0
4
0
Order By: Relevance
“…This is counter to a recently postulated hypothesis. (Goischke, 2019) We have shown that the risk of autoimmune disease following alemtuzumab is higher for women (HR 3.6). This risk factor has been noted previously.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This is counter to a recently postulated hypothesis. (Goischke, 2019) We have shown that the risk of autoimmune disease following alemtuzumab is higher for women (HR 3.6). This risk factor has been noted previously.…”
Section: Discussionmentioning
confidence: 90%
“…(Li et al, 2016) As noted above relative vitamin D deficiency is a risk factor for MS and this has also been noted for a number of other autoimmune diseases (see Table 1). (Xu et al, 2015;Lee and Bae, 2016;Islam et al, 2019;Feng et al, 2015;Penna-Martinez et al, 2018;Klack and Carvalho, 2010;Antico et al, 2012;Orgaz-Molina et al, 2012) This has led some to speculate that vitamin D deficiency might be a potentially modifiable factor in the development of autoimmune disease following alemtuzumab for MS. (Goischke, 2019) We have undertaken a retrospective case-control study of vitamin D levels in a cohort of people with MS treated with alemtuzumab with the aim of identifying factors associated with an increased risk of autoimmune disease. The primary hypothesis being tested is that the occurrence of autoimmune disease following alemtuzumab therapy will be associated with lower levels of vitamin D in the peri-and post-treatment phase.…”
Section: Introductionmentioning
confidence: 99%
“…This is related to the well-known effects of VD, both on the hair follicle and on the immune system. In particular, VD levels are negatively associated with IL-21 and IL-17 concentrations [ 13 ]. In turn, these proinflammatory cytokines have been shown to induce Th17 cells and inhibit the re-differentiation of regulatory T cells, playing an important role in the development of many autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms lead to a decline in the production of inflammatory cytokines, such as IL-12 and IL-17, and to an increase in anti-inflammatory cytokines, such as IL-10 [31]. VD also exerts its anti-inflammatory effects on monocytes, macrophages, and dendritic cells [32]. Due to these mechanisms, vitamin D deficiency has been associated not only with MS, but also with numerous other autoimmune, oncological, infectious, and cardiovascular diseases [33].…”
Section: Introductionmentioning
confidence: 99%